Growth, Development, and Mineral Nutrient Accumulation and Distribution in Tulip from Planting through Postanthesis Shoot Senescence. (2nd August 2015) - Niedziela, Carl E.; Nelson, Paul V.; Dickey, David A.
Abstract : Tulips were grown under field conditions from mid-November through early-June. Plants were harvested and dissected into eight organs on twenty-one dates. These parts were dried, weighed, and analyzed for N, P, K, Ca, and Mg. A transition (as determined by curve join points) from a linear to a steep negative cubic response occurred prior to shoot emergence for N (82 days after planting (DAP)), at shoot emergence for K (93 DAP) and Ca (94 DAP), and after shoot emergence for Mg (102 DAP) and dry matter (118 DAP). A transition from a linear to a steeper linear response occurred at shoot emergence for P (93 DAP). Growth, organ development, and nutrient accumulation occurred continuously from planting to maturity (188 DAP), except for K which did not accumulate during the initial linear phase. Since the increase in accumulation of all five nutrients preceded the dry matter accumulation, these nutrients could be used as predictors in growth models. Practical implications from this study include the importance of maintaining soil Ca levels through liming and applying the N, P, and Mg as split applications with smaller rates at planting and larger rates at emergence. The entire K application may be applied at emergence.